Anguaks in Copper and Netsilik Inuit Spirituality - Pollick, Jason (2020)
The composition of and dynamics underlying the use of anguaks are described in great detail. The discussion is largely confined to the Copper and Netsilik Inuit, although several other groups are touched on by way of comparison. The work consists firstly of a summary and interpretation of Rasmussen's (1931) chapter devoted to Netsilik anguaks. This material is then synthesized with material collected over the course of several participant-focused interviews conducted with seven Inuit elders from the community of Cambridge Bay. For clarity of presentation, several factors have been distinctly considered: the material composition of anguaks derived from animals, anguaks relating to human beings, women's objects, and shamanic paraphernalia. Based on these findings, a sample of 15 artifacts from the Canadian Museum of Civilization Corporation's collections are interpreted and discussed.